SIMULASI MODEL ANTRIAN OPTIMAL LOKET PEMBAYARAN PARKIR (Jurnal Inovisi (Teknik Industri), 2016)
AbstractThe purposeof this researchis to determine whether the number of motorcycle parking checkouts at Esa Unggul University is optimal in serving all customers. While the specific objectives of this research was to find out how many motorcycle checkouts amount of parking that should be owned by Esa Unggul University so that it can serve customers optimally. To solve that problem and obtain the expected goals, so in this research using the queue model to determine the performance of the parking checkouts. In addition, simulation techniques are also used to provide an overview of areal system in order to evaluate and improve system performance. From the calculation and simulation ProModel obtained that the optimal number of counters for motorcycle parking payment counter at Esa Unggul University is as much as 2 counters. So the performance of the queue for the current conditions that exist at the University of Esa Unggul especially on motorcycle parking payment counter that uses 2 counters were optimal. From the calculations, the level of service and optimal performance of the queue contained in M = 2 (the number of motorcycle parking payment counter as much as 2 counters) with details of its performance are P0 (the probability of no customers/motors in the queuing system) is 0.3249 ; Ls (number of customers/average motor in the queuing system) is 1.4257 ; Ws (the average time spent on customer/motors in line or being served) is 0.0475 ; Lq (number of customers/average motor waiting in the queue) is 1.4749 ; dan Wq (the average time spent by the customer/motor to wait in the queue) is 0.0492. From the ProModel simulation results obtained service levels and optimal performance of the queue contained in 2 Line/Lane Model with an % Idle average value of 51.17. Keywords: Queue, Queue Systems, Modeling, Simulation, Model AbstrakTujuan penelitian ini yaitu untuk mengetahui apakah jumlah loket pembayaran parkir motor di Universitas Esa Unggul sudah optimal dalam melayani seluruh pelanggan. Sedangkan tujuan khusus dari penelitian ini adalah untuk mengetahui berapa jumlah jumlah loket pembayaran parkir motor yang sebaiknya dimiliki oleh Universitas Esa Unggul sehingga dapat melayani pelanggan secara optimal. Untuk mengatasi permasalahan tersebut dan memperoleh tujuan yang diharapkan, maka dalam penelitian ini digunakan model antrian untuk mengetahui kinerja loket pembayaran parkir. Selain itu teknik simulasi juga digunakan untuk memberikan gambaran dari suatu sistem nyata dalam rangka mengevaluasi dan meningkatkan kinerja sistem. Dari hasil perhitungan dan simulasi ProModel diperoleh bahwa jumlah loket optimal untuk loket pembayaran parkir motor di Universitas Esa Unggul adalah sebanyak 2 loket. Sehingga kinerja antrian untuk kondisi saat ini yang ada di Universitas Esa Unggul khususnya pada loket pembayaran parkir motor yang menggunakan 2 loket sudah optimal. Dari hasil perhitungan diperoleh tingkat pelayanan dan kinerja antrian optimal terdapat pada M = 2 (jumlah loket pembayaran parkir motor sebanyak 2 loket) dengan rincian kinerjanya adalah P0 (probabilitas tidak adanya pelanggan/motor dalam sistem antrian) sebesar 0.3249 ; Ls (jumlah pelanggan/motor rata-rata dalam sistem antrian) sebesar 1.4257 ; Ws (waktu rata-rata yang dihabiskan pelanggan/motor dalam antrian atau sedang dilayani) sebesar 0.0475 ; Lq (jumlah pelanggan/motor rata-rata yang menunggu dalam antrian) sebesar 1.4749 ; dan Wq (waktu rata-rata yang dihabiskan oleh pelanggan/motor untuk menunggu dalam antrian) sebesar 0.0492. Dari hasil simulasi ProModel diperoleh tingkat pelayanan dan kinerja antrian optimal terdapat pada Model 2 Jalur/Lajur dengan nilai rata-rata % Idle sebesar 51.17. Kata kunci: Antrian, sistem antrian, pemodelan, simulasi, model